2023
DOI: 10.1111/ejh.14047
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric antigen receptor T cells for acute myeloid leukemia

Abstract: The use of T cells expressing chimeric antigen receptors (CARs) that can target and eliminate cancer cells has revolutionized the treatment of B‐cell malignancies. In contrast, CAR T cells have not yet become a routine treatment for myeloid malignancies such as acute myeloid leukemia (AML) or myeloproliferative neoplasms (MPNs). For these disease entities, allogeneic hematopoietic cell transplantation (allo‐HCT) relying on polyclonal allo‐reactive T cells is still the major cellular immunotherapy used in clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 86 publications
(155 reference statements)
0
3
0
Order By: Relevance
“…Challenges in the myeloid space include the identification of antigens which can be targeted on leukemic clones while sparing healthy hematopoietic stem cells and precursors. Recent advances in target identification and selection are showing promise in realizing this specificity, and we refer readers to a recent review summarizing this rapidly evolving field ( 200 , 201 ). Yao and colleagues report a case utilizing donor CD123 CAR-T as part of reduced intensity conditioning prior to haploidentical transplantation in a highly aggressive leukemia relapsing post allogeneic transplantation ( 153 ).…”
Section: Novel/unapproved Agentsmentioning
confidence: 99%
“…Challenges in the myeloid space include the identification of antigens which can be targeted on leukemic clones while sparing healthy hematopoietic stem cells and precursors. Recent advances in target identification and selection are showing promise in realizing this specificity, and we refer readers to a recent review summarizing this rapidly evolving field ( 200 , 201 ). Yao and colleagues report a case utilizing donor CD123 CAR-T as part of reduced intensity conditioning prior to haploidentical transplantation in a highly aggressive leukemia relapsing post allogeneic transplantation ( 153 ).…”
Section: Novel/unapproved Agentsmentioning
confidence: 99%
“…Acute myeloid leukemia (AML) comprises a group of acute hematologic malignancies that arise from myeloid precursor cells and is often associated with a variety of genetic aberrations. As AML is the second most common type of leukemia in adults, there are numerous approaches to make this type of disease feasible to CAR-T-cell therapy ( 108 , 109 ). Previous studies using CAR-T-cell therapy in AML patients have shown that the technique could prove a potentially valid strategy for patients with relapsed or refractory disease ( 110 114 ), a patient group that currently has only very limited therapy options.…”
Section: Acute Myeloid Leukemiamentioning
confidence: 99%
“…However, chemotherapeutic treatment is generally not curative as a typically small fraction of the malignant cells remains and eventually fuels disease recurrence 8 . There is a widespread hope that the recent introduction of targeted therapies or immunotherapies can improve treatment success by specifically eliminating cells with certain genetic mutations or enhancing the immune system's ability to fight the malignant cell pool [11][12][13] . However, as of now the only curative option for AML patients is allogeneic hematopoietic stem cell transplantation (SCT).…”
Section: Introductionmentioning
confidence: 99%